The Effect Of Academic Service Quality On Satisfaction And Loyalty Of Students University - Angrian Permana*; M. Havidz Aima; Eny Ariyanto; Adi Nurmahdi (LPPM Universitas BSI, 2020)
ABSTRACTThis aims is to determine the factors of academic service quality and analyze the relationship between academic service quality to student satisfaction and loyalty at Bina Bangsa University. This is explanatory research with the population of the students of Bina Bangsa University odd semester, academic year 2018/2019. The research sample uses purposive sampling with a total of 200 respondents. Data were analyzed with the Equation Model Structure (SEM) consisting of measurement models and structural models. It can be concluded that improving the quality of the system will be able to influence student satisfaction but not necessarily be able to increase student loyalty directly. Indirectly through student satisfaction, student loyalty can be increased through the quality of the system. Improving the quality of information both directly and indirectly can affect student satisfaction and loyalty. Quality of service at a tertiary institution becomes very important in increasing student satisfaction and loyalty. Keywords: Satisfaction; Loyalty; Quality of academic services.